PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “SIBANGTAR (NUMERASI KELILING BANGUN DATAR)’’ PADA SISWA KELAS V SD - Nova Oktavia Sari; Dra. Dian Kusmaharti, S.Si., M. Pd (STKIP Subang, 2025)
Interactive learning media is a learning media designed to actively involve students in the learning process. This study aims to develop interactive learning media on the material of the circumference of flat shapes in grade V of elementary school. This study uses the ADDIE research model with several stages including Analysis, Design, Development, Implementation, Evaluation. This study created an interactive learning media based on android with an assessment from three validators, namely material experts with a value of 94%, media experts with a value of 90%, and language experts with a value of 90% all meeting the criteria of